Les cordées de la réussite, intentions et effets d’un dispositif pour l’égalité des chances - Sophie Kennel (Éducation et Socialisation)
This paper examines the intentions and effects of the "Cordées de la réussite" schemes, which aim to promote social mobility in higher education. A qualitative study conducted at the University of Strasbourg shows that students enrolled in the Cordées de la réussite already demonstrate academic ambition before entering the program and have a strong potential for academic achievement. The Cordées de la réussite would thus constitute an early model of meritocracy.